(untitled) (Tecnología y Sociedad, 2019)
The technological risk is certainly a controversial issue, as demonstrated by the loud debate between environmental organizations and technology- promoting companies. In the core of the debate is the capability of science to settle the debate. On the one hand its objectivity is questioned. On the other hand the risk aspect brings back the issue of subjectivity. Even if science would achieve a comprehensive and objective assessment of the probability and the magnitude of the potential damage that a specific technology may cause, the people attitude is subjective in nature; then the right decision is also subjective. One society can tolerate a risk to get the corresponding benefits from technology while another society would not. The environmental economics makes a valuable contribution to this issue. By means of sophisticated methods it can measure and integrate the subjective element of the risk assessment in the analysis of the technological risk; making it possible to take into account the society member attitudes towards risk in the scientific analysis.